(untitled) (INNOVATIVE ECONOMY, 2022)
Yarovyi K.O., Honchar L.V., Babaian D.P. INFORMATION SYSTEMS AND TECHNOLOGIES AS AN INTEGRAL PART IN THE MANAGEMENT OF THE ENTERPRISE Purpose. The aim of this article is to research the features of use of modern information systems and technologies in activity of the enterprises for increase of efficiency of administrative decisions. Methodology of research. The methodological basis of the study was scientific methods of cognition based on a systematic approach to solving problems. To achieve this goal and obtain the results of the study different general and special scientific research methods are used: dialectical; monographic (in processing scientific publications); system analysis (in the study of the current state of use of information systems and technologies in the management of the enterprise); abstract and logical (to substantiate the key characteristics of modern information systems and technologies); comprehensive analysis (in forming conclusions and proposals for solving tasks) and others. Findings. The analysis of the current state of use of information systems and technologies in the management of the enterprise is carried out. It is established that one of the effective directions of improving the management of the enterprise is the development and implementation of modern information systems and technologies. The tasks performed by information systems and technologies in managerial activity are revealed. The basic principles and conditions of implementation of information systems and technologies at the enterprise are analysed. The main factors influencing the implementation of information systems and technologies at the enterprise are identified. The main functional subsystems that can be contained in the information system of the enterprise are presented. Originality. The study of the peculiarities of the introduction and use of modern information systems and technologies in the activities of enterprises to improve the efficiency of management decisions was further developed. Practical value.The obtained results of the study will help to timely and efficient analysis and forecasting of economic activity of the enterprise. Key words: information systems; information technologies; technological processes; information process; information products.